Inclusive Education in Higher Education Students: A Systematic Review in Scopus and Web of Science Between 2019 And 2023 - Salas-Torres, Lissette Margarita; Joo, Luis Alexander Pulido; Yanayaco, Liliana Morales; Canchari-Preciado, Miguel Ángel; Chacón, Luis Fernando Espejo; Saldaña-Millan, Jackeline Margot; Torres-Solano, Carol Giovanna (International Journal of Membrane Science and Technology, 2023)
This study performs a systematic review of the literature on inclusive education in higher education students. The research followed the guidelines of the PRISMA methodology for the identification of records in the Scopus and Web of Science (WoS) databases during the period 2019 to 2023. During the information search process, a total of 199 records were found. From both databases, which after going through rigorous inclusion and exclusion criteria, 17 investigations were finally obtained that were included for the review. The included studies sought to answer the research question: What factors are important to promote inclusive education as a pedagogical model in higher education students? According to the information found in the systematization of the articles, 2 tables of contents were generated that show the authors, countries/regions according to the corresponding author, the keywords of the studies, the dimensions, instruments, study approaches, strategies of execution and conclusions of the studies in order to contrast data to find strengths or weaknesses in the studies that support answering the research question. The results showed that Spain is the leading country in publication with corresponding authors, with 82.4% of all studies. Likewise, 47.01% of the studies presented a quantitative approach. On the other hand, educational strategies stand out such as: the use of digital resources (videoconference), the use of ApS (Service-Learning), civic moral disconnection and didactic strategies (physical activities), since they aim to develop dynamics of academic development, cognitive, social and professional with the aim of promoting inclusive education in higher education students. Another factor to consider is the positive attitude of teachers towards disability and cultural diversity, so that they promote inclusion in their practices. In this way, it is concluded that, to promote inclusive education in higher education students, the following should be considered: teacher support, the use of innovative educational strategies and the open participation of all students in inclusive activities to promote a diverse education atmosphere in order to support students with physical, mental, sensory disabilities or cultural differences to obtain professional training.